1995
DOI: 10.1210/jcem.80.8.7629229
|View full text |Cite
|
Sign up to set email alerts
|

Core body temperature and circadian rhythm of hot flashes in menopausal women.

Abstract: Postmenopausal hot flashes are characterized by sweating and peripheral vasodilation and occur more frequently during increased heat loads. The circadian rhythm of core body temperature (TC) is well known and suggests that hot flashes will be most frequent when core temperature is highest. This hypothesis has not been tested previously. Ten symptomatic and six asymptomatic postmenopausal women were recruited from advertisements and screened. Each received 24-h ambulatory monitoring of sternal skin conductance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 16 publications
2
65
0
1
Order By: Relevance
“…We did not observe an increase in time spent in stage N1, but there may not have been enough objective hot flashes per night to detect a change in N1. Alternatively, the transient increase in core body temperature of up to 0.1°C that usually precedes each flash may also induce an awakening, [19][20][21] as has been observed in other clinical settings. 22 However, it is also plausible that N1 sleep and brief awakenings are more closely linked with hot flashes because neural factors that drive wakefulness also increase susceptibility to hot flashes, which are similarly triggered by cortical activation.…”
Section: Discussionmentioning
confidence: 92%
“…We did not observe an increase in time spent in stage N1, but there may not have been enough objective hot flashes per night to detect a change in N1. Alternatively, the transient increase in core body temperature of up to 0.1°C that usually precedes each flash may also induce an awakening, [19][20][21] as has been observed in other clinical settings. 22 However, it is also plausible that N1 sleep and brief awakenings are more closely linked with hot flashes because neural factors that drive wakefulness also increase susceptibility to hot flashes, which are similarly triggered by cortical activation.…”
Section: Discussionmentioning
confidence: 92%
“…Venous blood-samples were taken for analysis of Testosterone (T), Follitropin (FSH), Lutropin (LH), Sex Hormone Binding Globulin (SHBG), albumin and capillary haemoglobin (Hb) and Bio-available Testosterone (BT) was calculated [20].…”
Section: Methodsmentioning
confidence: 99%
“…Studies by Freedman et al, using an ultrasensitive temperature probe, suggest that hot flushes are triggered by small elevations in core body temperature (Tc) acting within a narrowed thermoneutral zone in symptomatic postmenopausal women (3). This group found that small but significant elevations in Tc precede most (76%) hot flush episodes (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…This group found that small but significant elevations in Tc precede most (76%) hot flush episodes (3)(4)(5). These same investigators subsequently found that postmenopausal women with hot flushes had a narrower thermoregulatory zone (0°C) compared with postmenopausal women who do not flush (0.4°C).…”
Section: Introductionmentioning
confidence: 99%